Actividad de un “ensamblaje” de murciélagos en el norte de Brasil (Mammalia: Chiroptera) - Durán de la Ossa, Adrián Alonso (2019)
The Amazon is considered one of the most biodiverse tropical ecosystems in the world thanks to the structural complexity that geology offers and the great biological richness of its soils. Further, concerning the Mammalian class, bats are one of the best represented taxa in the region, nevertheless their ecology is poorly studied. This study, evaluates the influence of environmental factors such as the climate season, temperature (maximum and minimum), relative humidity and lunar phase on the activity patterns (abundance and trophic guilds) of an assemblage of bats in the Brazilian central Amazon. This study was carry out in two municipalities of the state of Rondônia using eight mist nets during 62 nights of sampling, covering humid and dry periods. A total of 2 499 individuals of 58 species were captured. The best represented family was the Phyllostomidae, while the species that recorded the highest frequency of captures was Carollia perspicillata (N = 859), followed by C. brevicauda (N = 209). There were no significant differences between the structure of the assemblage considering the climatic season (raindry). However, during the dry season a greater number of species and individuals was recorded (57 species, N = 1 597) than in the rainy season (44 species, N = 902). The abundance of bats was influenced mainly by relative humidity (P = 0.00) and minimal temperature (P = 0.04), while the species responded differentially to the lunar phase. These results show the influence of environmental factors on the activity patterns of a bat assemblage in the Amazon, where the factors that influence them depends on the ecology of each species. However, studies carried out for longer periods are required to determine if these patterns are maintained over time.